Sympozjum Naukowe Instytutu Ekonomiczno-Przyrodniczego „MarGo” nt. „Młodzi dla nauki, ekonomia – nauki społeczne – – rolnictwo – ochrona środowiska”: Scientific Symposium of the Institute of Economic and Natural Sciences "MarGo" „Young for science, economics – social science – – agriculture – environmental protection” - Czapski, Piotr (Management and Administration Journal, 2021)
x